The Contribution of Nusantara Moslem Local Tradition on Micro Finance Risk Management in Indonesia - Hidayat, Nur (International Journal of Islamic Business and Economics (IJIBEC), 2017)
The aim of the study is to explore the local tradition in Bondowoso Pendhalungan society which bases consideration in the risk management of the micro finance sector in Bondowoso. The method of this study was qualitative research used grounded method. We collected data through participatory observation for 3 years from 2013 until early 2016, semi−structured interviews and literature studies. The results showed the gap that the banks early warning sign (EWS) only considered the financial aspects, the non−financial aspect and transaction aspect, not concerning the cultural aspects. Based on the results of the research, it was found that financial performance in the form of loans, deposits and credit quality (non−performing loans) were affected by the implementation of local cultural tradition. From the results of the study, researchers gave suggestions for banking in Bondowoso and in Indonesia to consider aspects of the local culture or local wisdom as the basis of consideration of banking operations strategies in each region in Indonesia.